Breastfeeding empowerment and its relationship with health literacy and spousal support among breastfeeding mothers in Tabriz, Iran: a cross-sectional study - Mojgan Mirghafourvand; Mina Hosseinzadeh; Shaqayeq Targhaq; Zahra Mousavi (BMJ Open)
Background Breast milk is crucial for the health and survival of infants, but exclusive breastfeeding often fails due to various reasons such as lack of breastfeeding empowerment.Objectives This study aimed to determine the status of breastfeeding empowerment and its relationship with health literacy and perceived spousal support among breastfeeding mothers while recognising that other related factors also contribute to breastfeeding empowerment.Design Cross-sectional study.Setting Primary health centres of Tabriz city, Iran.Participants Included 342 breastfeeding mothers with infants aged 6 months or younger in Tabriz, Iran.Results The mean (SD) scores for breastfeeding empowerment, health literacy and partner support were 141.98 (33.92) out of a possible range of 37 to 185, 126.08 (21.27) out of a possible range of 33 to 165 and 64.95 (12.62) out of a possible range of 20 to 100, respectively. Based on the adjusted general linear model, for every unit increase in perceived spousal support, women’s breastfeeding empowerment score increased significantly (B=0.546; 95% CI 0.29 to 0.79; p<0.001). Additionally, working mothers had a significantly higher breastfeeding empowerment score compared with housewives (B=13.91; 95% CI 0.88 to 27.73; p=0.04), and currently, breastfeeding mothers had a significantly higher score compared with mothers who were not currently breastfeeding (B=72.26; 95% CI 60.42 to 84.10; p<0.001).Conclusions The findings of this study underscore the critical role of perceived spousal support in enhancing breastfeeding empowerment among mothers. By encouraging spousal involvement, families can create a supportive environment that values and facilitates breastfeeding. Healthcare providers also can play an essential role in offering guidance and resources to both mothers and their partners. By emphasising the importance of spousal support in breastfeeding, a supportive culture can be fostered that values breastfeeding as a natural aspect of motherhood.